Anomaly of the inferior vena cava and lactose malabsorption - Schnedl, W. J.; Kalmar, P.; Wallner-Liebmann, S. J.; Reiter, G.; Mangge, H.; Lipp, R. W. (Phlebologie, 2016)
Patients with anomalies of the inferior vena cava (IVC) are rare, are usually asymptomatic and this developmental anomaly is detected during radiologic evaluation of deep vein thrombosis or incidentally during abdominal radiologic evaluation. We report on time resolved three-dimensional magnetic resonance angiography (4D MRA) in a patient with congenital anomaly of the IVC and nonspecific abdominal complaints. 4D MRA is shown for evaluation and detailed diagnosis in vascular venous anatomy. However, due to continuing bloating and irregular bowel movements we investigated carbohydrate malabsorption and a lactose malabsorption was diagnosed. The nonspecific abdominal complaints in this patient with IVC anomaly were due to lactose malabsorption and were treated successfully with a lactose-free diet.@Supplementary material online: www.phlebologieonline.de: http://dx.doi.org/10.12687/phleb2285-1-2016
Keywords: Inferior vena cava anomaly; magnetic resonance imaging; nonspecific abdominal complaints; lactose malabsorption